Angiogenesis controlling mechanisms and their clinical application in advanced cases of colorectal cancer - Kozaczka, Anna; Woszczyk, Dariusz; Najda, Jacek (Contemporary Oncology/Współczesna Onkologia, 2004)
In the face of the conventional chemotherapy failure, investigations into novel, alternative therapeutic options for advanced clinical stages of colorectal cancer are being performed. In spite of the introduction of new cytoreductive drugs, there was no significant and satisfactory improvement of inoperative stage patients survival observed so far. Being aware of the tumor mass proliferation rate dependence on the process of neoplastic vessel network formation, the identification process of neoplastic angiogenesis stimulators was initiated. The vascular endothelial growth factor (VEGF) was confirmed beyond doubt to be involved in this process, what triggered therapeutical trials with agents inhibiting its mechanisms of action. Many clinical trials were undertaken to determine the therapeutic value of angiostatins, like bevacizumab, thalidomide, INF-alpha and marimastat. Bevacizumab was proved to be the most promising agent, being a unique antibody specifically binding VEGF. A single dose of this substance was confirmed to reduce the volume of the tumor vascular network, effectively reducing blood perfusion of neoplastic tissue. Simultaneously, extensive experimental and epidemiological studies are being carried out to identify factors, yet unknown, that naturally influence the tumor proliferation rate. Among them considerable attention is paid to cyclooxygenase-2 (COX-2) inhibitors, routinely administered as analgesic or antiinflammatory agents. Their antineoplastic activity was proved in the context of colorectal cancer and other epithelial neoplasms, related to COX-2 activity inhibition, engaged in carcinogenesis. In the nearest future, the problem of COX-2 involvement in the process of neoplastic proliferation and the consequences of its chronic inhibition are likely to be the main theme of numerous investigations.